2019
DOI: 10.36348/sijap.2019.v02i10.007
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Practical Examination Techniques in Osteology for First-Year MBBS

Abstract: This complete enumeration, cross-sectional comparative study was conducted to compare the scores obtained by students in traditional practical examination with that obtained in objective structured practical examination in Osteology, which is a "must know" component of the first-year MBBS curriculum in Anatomy. After obtaining permissions from the Institutional Ethics Committee and institutional authorities for conducting the study, first-year MBBS students were oriented about the purpose of the study, the obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Furthermore interaction with 3D models led to a better understanding of the shape and spatial relationships among structures and helped illustrate anatomical variations from one body to another (Pujol et al, 2016) In the present study, no gender difference in student's performance when taught biology with the 3D model. In contrast, another study Kamkhedkar et al (2017), has reported that females scored better than males when taught with 3D models. This shows that the use of a 3D model benefits a gender to the other.…”
Section: Discussionmentioning
confidence: 85%
“…Furthermore interaction with 3D models led to a better understanding of the shape and spatial relationships among structures and helped illustrate anatomical variations from one body to another (Pujol et al, 2016) In the present study, no gender difference in student's performance when taught biology with the 3D model. In contrast, another study Kamkhedkar et al (2017), has reported that females scored better than males when taught with 3D models. This shows that the use of a 3D model benefits a gender to the other.…”
Section: Discussionmentioning
confidence: 85%